How the GCC Economic Crises Effect Labor Migration: Evidence from Pakistan - Khan, Yasir; Mingyi, Wang (Asian Journal of Economics and Empirical Research, 2018)
Migrant workers have participated in promoting economic growth and prosperity and the generation of wealth in countries of destination. The Gulf Cooperation Council (GCC) which is comprised of six countries such as Saudi Arabia, UAE, Qatar, Kuwait, Bahrain, and Oman have been historically and traditionally job market for Pakistani workers. Labor migration and its relationship to economic growth and employment have received increasing attention because of increasing demand for labor, higher salaries, economic and political stability. Using a case study, we focus on the impact and relationship of labor migration with macroeconomic indicators such as Gross Domestic Product (GDP), unemployment, and inflation rate. Limited employment opportunities, the weak economy, and political instability are the factors leading labor migration from Pakistan. Consequently, the government of Pakistan considered labor migration primarily as an employment sector and encourage labor migration to solve economic problems in the country. We analyze the impact of labor migration on (GDP), Inflation rate and unemployment in Pakistan with the help of time series data from 1971-2016. The result to have showed a positive and significant relationship between labor migration and GDP, while a negative but significant relationship with unemployment. On the other hand, there is no relationship between labor migration and inflation rate. we found that the GCC economic crises actually caused significant influence on labor migration in the case of Pakistan.